Forensic Monitoring Project Report: Kiseljak Exhumations of Federal Commission on Missing Persons Croat Side - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Kennedy, Brenda On 19 March 1998 the Federation Commission on Missing Persons Croat Side exhumed the remains of two individuals from a cemetery in Bilalovac. Excavations were also conducted at a second purported grave site in a cemetery in Zabrđe but no human remains were found at this site. Place of Exhumation: Kiseljak Exhumation Site: Bilalovac, Zabrđe Date of Exhumation: 19 March 1998 Minimum Number of Exhumed Individuals: 002